Estudio socio-económico de los emprendimientos y su impacto en el nivel de ingreso de las familias del Recinto Fumisa, cantón Buena Fe, año 2014 - Ipáz Vélez, Evelyn Estefanía (2015)
The present study was the delimitation Ecuador, and its unit of study Fumisa Campus, cantón Buena Fe. Once defined the research topic "socio-economic study of entrepreneurship and its impact on the income level of families Campus Fumisa, cantón Good Faith, 2014," proceeded to analyze your problem areas, justifying the conduct the present study. Defined objectives, assumptions, and the independent and dependent variables of the research, theoretical framework, where different issues were addressed objectively developed. We proceeded to the collection of data through surveys of entrepreneurial families and non-entrepreneurial Fumisa Campus. The results were analyzed and interpreted, and also allowed to test the hypothesis of the research, namely: Implementation of the socio-economic survey of the enterprises will reveal how they influence the enterprises in the level of household income Campus Fumisa, cantón Buena Fe, 2014. The conclusions were reached determine that enterprises generate a positive impact on the level of income and quality of life of entrepreneurial families Fumisa Campus. And also allowed to meet the needs and problems of entrepreneurs.